1986
DOI: 10.1111/j.1445-2197.1986.tb02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentum Patellae Rupture Following Local Steroid Injection

Abstract: Ligamentum patella rupture following local steroid injection in an Australian Rules footballer is described. The relationship between local steroid injection and rupture of large ligaments and tendons is reviewed. Careful consideration prior to steroid injection is strongly suggested because of the risk of rupture of these structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Many investigators have reported case examples of tendon ruptures, especially among athletes, from injections of corticosteroid (7,8,87,(94)(95)(96)(97)(98)(99)(100). The question remains whether these ruptures are the effect of steroids or merely a final manifestation of the disease for which the steroids were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have reported case examples of tendon ruptures, especially among athletes, from injections of corticosteroid (7,8,87,(94)(95)(96)(97)(98)(99)(100). The question remains whether these ruptures are the effect of steroids or merely a final manifestation of the disease for which the steroids were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Alexeeff (96) reported a case of rupture of the patella tendon in a young athlete with symptoms of Jumper's knee in 1 year. He had two corticosteroid injections that settled the symptoms and he resumed his normal training activities.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported examples of tendon ruptures (included patellar tendons), especially among athletes, from injections of corticosteroids (77)(78)(79)(80)(81)(82)(83). The question remains whether these ruptures were the effect of steroids or merely a manifestation of the disease for which the steroids were used.…”
Section: Diagnosismentioning
confidence: 99%
“…They are often associated with trauma. However, there are reports relating to local injection of steroids and a large number of systemic diseases such as systemic lupus erythematosus, diabetes mellitus, rheumatoid arthritis, osteomalacia and chronic kidney failure 4, 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%